Editorial - Ruiz Sánchez, Javier; Bertin, Mattia (Urban, 2016)
In the last week of June 2014, the Second International Conference New Urban Languages took place in Madrid.While the first conference under this topic, held in Milan in 2013, chose “Reimaging the City after the Knowledge-based Turn” as its motto, the conference in Madrid, “Rethinking Urban Ideology in Post-Ideological Times”, was aimed at reimagining present and future cities through the lense of urban ideologies. Therefore, the two main questions presented during the Conference were: Why do we need to talk about urban ideology now? and What can be understood as urban ideology, what is urban ideology?